Autoritarismus und soziale Dynamiken: Karen Stanners Modell der autoritären Dynamik als Beitrag für religionspädagogische Reflexionen zur Demokratiebildung - Feichtinger, Christian (Österreichisches Religionspädagogisches Forum, 2025)
Political education and democracy education have increasingly become the focus reflections also in religious education. A particular sign of the times is the rise of right-wing populist actors in particular, and to a lesser extent left-wing populist actors, who strategically rely on authoritarianism as a strategy of persuasion and domination. Populism and authoritarianism therefore represent a central challenge both for the educational system as a whole and for civic and religious education. Australian political scientist Karen Stenner analyzed and to a certain extent predicted the rise of authoritarian and populist politics in her major work "The Authoritarian Dynamic" back in 2005. What is fruitful about her approach is that she assumes an interplay of social dynamics on the one hand and psychological predispositions on the other, which makes it necessary to deal with authoritarian personality/character types. Due to the specific psychological predispositions, according to Stenner, authoritarianism remains a permanent challenge to democracy that cannot be fully countered by education. The article brings Stenner's approach into conversation with current perspectives on religious education for democracy and shows how the needs and perspectives of learners with authoritarian tendencies can be addressed in religious learning processes.